Strategi Implementasi Manajemen Berbasis Sekolah - Rakhil Fajrin (Intizam, Jurnal Manajemen Pendidikan Islam, 2018)
Implementation of School Based Management includes: Curriculum management, personnel management, student management, funding / finance management, community relations management, and specialized service management including libraries and UKS. In every field, the implementation of School Based Management has been implemented in accordance with the work program planned and compiled by the school, so that the school program can be achieved and run well. Strategies in School-Based Management Implementation (SBM) should involve all school stakeholders in decision-making. So when determining school strategies to improve the quality of education through the implementation of School Based Management (SBM) is done together. In determining the strategy. The first step is to determine the vision, mission and goals of the school. The second step identifies the school's real challenge. The third step identifies the functions needed to achieve the goal. The fourth step is to use SWOT analysis to solve problems in developing school plans and programs in which to improve the quality of education. The fifth step of implementing the quality improvement plan is then to monitor and evaluate the implementation.